LITERATURE STUDY OF ANTIBACTERIAL ACTIVITY OF THE FAMILI RUTACEA - Nurfadila, Nurfadila; Kosman, Rachmat; Herwin, Herwin (Fakultas Farmasi, Universitas Muslim Indonesia, 2022)
Indonesia has one of potential plants as an herbal medicine, called Lime (Citrus aurantifolia) and Kaffir Lime (Citrus hystrix DC), both used for different purposes such as cooking, seasoning and traditional medicine. Both plants are derived from the family of Rutaceae which belongs to shrubs that have many branches and twigs. This study aimed to carry out the antibacterial assay of the Rutaceae family. This study used a literature study approach, which references were obtained through 3 Journal sources, namely Google scholar, pubmed, and thscience direct. Furthermore the selected research article which met the criteria was reviewed. Based on the search done, it obtained 7 articles and identified antibacterial activity of lime and Kaffir Lime. The result confirmed that both have antibacterial compounds against bacteria Escherichia coli, and Staphylococcus aureus because they contain secondary metabolite compounds consisting of alkaloids, flavonoids, tannins, and essential oils.